Neonatal and Infantile Immune Responses to Encapsulated Bacteria and Conjugate Vaccines. (23rd September 2008) - Klein Klouwenberg, Peter; Bont, Louis
Abstract : Encapsulated bacteria are responsible for the majority of mortality among neonates and infants. The major components on the surface of these bacteria are polysaccharides which are important virulence factors. Immunity against these components protects against disease. However, most of the polysaccharides are thymus-independent (TI)-2 antigens which induce an inadequate immune response in neonates and infants. The mechanisms that are thought to play a role in the unresponsiveness of this age group to TI-2 stimuli will be discussed. The lack of immune response may be overcome by conjugating the polysaccharides to a carrier protein. This transforms bacterial polysaccharides from a TI-2 antigen into a thymus-dependent (TD) antigen, thereby inducing an immune response and immunological memory in neonates and infants. Such conjugated vaccines have been shown to be effective against the most common causes of invasive disease caused by encapsulated bacteria in neonates and children. These and several other approaches in current vaccine development will be discussed.